Analysis of Ship Operation Pattern Base on Bira - Pamatata Crossing - Wahidah, Jusma; Asri, Syamsul; Paroka, Daeng (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The Bira-Pamatata crossing transportation service is carried out by three ships, namely KMP Bontoharu, KMP Kormomolin, and KMP Balibo. These three ships have different technical specifications, so the cost of production for the three ships is also other at the 60% load factor level as the basis for determining the tariff. However, the tariffs set for the three ships remain the same. Therefore, it is necessary to decide on the basis of the ship's operating pattern that meets the operational feasibility criteria based on the value of the applicable tariff. The results of the frequency base based on the load factor between the three ships are for KMP Balibo as many as 770 trips/year, KMP Kormomolin as many as 464 trips/year, and KMP Bontoharu as many as 439 trips/year. The method used to determine the basic operating pattern equation approach is the trendline method based on the relationship between frequency and load factor that meets the feasibility of operations. The validation results show that the basic operating pattern equation for the three ships is feasible based on the correlation test results and the mean average percentage error so that the equation can be used as the basis for setting the operating pattern of the Bira -Pamatata crossing.